FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PENGAWAS PEMILU DI KABUPATEN KEPULAUAN TALAUD - MENAUNG, FANDY; NURMIATI, NURMIATI; ILHAM, ILHAM (Patria Artha Management Journal, 2024)
This research aims to determine the factors that influence the performance of electionsupervisors. This research is classified as population research using a questionnaire as adata collection tool. The population of this study was the Election Supervisory Board(BAWASLU) of Talaud Islands Regency with 37 people and the Election SupervisoryCommittee of Talaud Islands Regency with 19 people. Data were analyzed usingdescriptive statistical analysis using multiple linear regression analysis. The results ofdescriptive statistical analysis show that recruitment has a positive and significant effect,selection has a negative and insignificant effect, then compensation is positive andsignificant on the performance of Election Supervisors in Talaud Islands Regency andthese three variables have a simultaneous effect.